-5p-7=-(3p-3)-4p

Simple and best practice solution for -5p-7=-(3p-3)-4p equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5p-7=-(3p-3)-4p equation:


Simplifying
-5p + -7 = -1(3p + -3) + -4p

Reorder the terms:
-7 + -5p = -1(3p + -3) + -4p

Reorder the terms:
-7 + -5p = -1(-3 + 3p) + -4p
-7 + -5p = (-3 * -1 + 3p * -1) + -4p
-7 + -5p = (3 + -3p) + -4p

Combine like terms: -3p + -4p = -7p
-7 + -5p = 3 + -7p

Solving
-7 + -5p = 3 + -7p

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '7p' to each side of the equation.
-7 + -5p + 7p = 3 + -7p + 7p

Combine like terms: -5p + 7p = 2p
-7 + 2p = 3 + -7p + 7p

Combine like terms: -7p + 7p = 0
-7 + 2p = 3 + 0
-7 + 2p = 3

Add '7' to each side of the equation.
-7 + 7 + 2p = 3 + 7

Combine like terms: -7 + 7 = 0
0 + 2p = 3 + 7
2p = 3 + 7

Combine like terms: 3 + 7 = 10
2p = 10

Divide each side by '2'.
p = 5

Simplifying
p = 5

See similar equations:

| 4y^2-81x^2=-162x+405 | | .2x+2.4-12=0 | | x-7+(-99)=581 | | x-29=83 | | 41(52+13)=x+10-17 | | -5x^3+20x^2+20x+80=0 | | 91n^1+49n=0 | | 63n^2+63n=0 | | 15(x-4)=-6-9 | | -7x+4(3-5)=0 | | 10+x-.33333333x=0 | | 10+x-.33333333=0 | | x^2-15x+10=0 | | 5=2.5-4x | | x^6+8x^3+7=0 | | -1.5x=5 | | (3x+7)*(-8x-7)= | | 2.5-4x=5 | | .4+4x=5 | | 3k+13=19k-8 | | x-9y=19 | | ax-bc=a | | 12+2x-19=x+3 | | 5=0.4-4x | | 5=.5-4x | | 56v^2-23v=63 | | x+2-8=32 | | x+19+2x+27=10 | | (2w-4)/3=w-3 | | X+(X-35)+(X-46)+0.5=360 | | 140x+68=789 | | (X-5)+X+65=180 |

Equations solver categories